ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PEDAGANG IKAN DIPASAR FLAMBOYAN KOTA PONTIANAK - B21109026, WITA ARIANTO (Jurnal Pembangunan dan Pemerataan, 2016)
This study aims to determine the factor-factor that will influence the level of income of the merchant market flamboyant city of Pontianak on working capital (X1), work experience (X2) and working hours (X3). The method used in this research is descriptive analysis and research ekplanatory. This study uses primary data sourced from interviews and field observations were obtained directly from the merchant market flamboyant city of Pontianak. Based on the analysis, for the variables X1 and X2, H0 and H1 accepted, meaning that the variable working capital and working experience significantly affect pedapatan fish traders. For X3, H0 rejected H1 accepted, meaning that the number of working hours no real effect on revenue fish traders. Simultaneously, variable working capital, work experience and working hours significantly affect the income trader. Amounting to 64.9% of the change in income trader can be explained by changes in working capital variables, work experience and hours worked in unison. While the remaining 35.1% is explained by other variables not included as variables in the study. This is consistent with the study hypothesis. Given these observations suggested; that fish traders in Pontianak should pay more attention to working capital and work experience, karen variable working capital and working experience real influence revenue fish traders in Pontianak, such as by increasing working capital and broaden the work experience so that revenues fish traders in Pontianak can be increased. In addition, traders should also pay attention to the number of hours worked, namely by reducing working hours and labor.